The Effectiveness of Non-Litigation Dispute Resolution Mechanisms in Maintaining Legal Certainty and Justice in The Outsourcing Business of the Moving Consumer Goods Industry - Utardi, Utardi; Abustan, Abustan (UNIVERSITAS PAKUAN, 2017)
This study aims to analyse the effectiveness of non-litigation dispute resolution mechanisms in maintaining legal certainty for outsourcing companies in resolving employer obligations in the fast moving consumer goods industry; to analyse the effectiveness of non-litigation dispute resolution mechanisms in the context of employment or industrial disputes. The research method used is research, which means retrieval. The search in question is a search for true (scientific) knowledge, because the results of this search will be used to answer certain problems. In other words, research is a very valuable educational pursuit; it trains us to always be aware that there is much in this world that we do not know, and what we try to find, discover and know is still not the absolute truth. Article 1 point 10 of Law. No. 30 Year 1999, Disputes or differences of opinion through procedures agreed by the parties, namely out-of-court settlement by means of consultation, negotiation, mediation, conciliation, or expert judgement. The result of mediation that produces an agreement between the parties is referred to as a mediation agreement. This agreement will become legally binding if it has been set out in the form of a peace deed agreed by both parties, and if it has been ratified by the court, is binding on the parties and is implemented in good faith. Broad access for the parties to the dispute to obtain a sense of justice